2017
DOI: 10.1038/s41598-017-11409-4
|View full text |Cite
|
Sign up to set email alerts
|

HMGA1 regulates the Plasminogen activation system in the secretome of breast cancer cells

Abstract: Cancer cells secrete proteins that modify the extracellular environment acting as autocrine and paracrine stimulatory factors and have a relevant role in cancer progression. The HMGA1 oncofetal protein has a prominent role in controlling the expression of an articulated set of genes involved in various aspect of cancer cell transformation. However, little is known about its role in influencing the secretome of cancer cells. Performing an iTRAQ LC–MS/MS screening for the identification of secreted proteins, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…PLAU, urokinase-type plasminogen activator protease (uPA), is a secreted factor that binds to the outer cell surface, remodels the extracellular matrix, and then allows cells to move inside tissues. 53,54 Furthermore, PLAU is overexpressed in many cancer cells and is important for cancer cell metastatic spread. 28,55 MMP9 is involved in the breakdown of the extracellular matrix and promotes cancer cell metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…PLAU, urokinase-type plasminogen activator protease (uPA), is a secreted factor that binds to the outer cell surface, remodels the extracellular matrix, and then allows cells to move inside tissues. 53,54 Furthermore, PLAU is overexpressed in many cancer cells and is important for cancer cell metastatic spread. 28,55 MMP9 is involved in the breakdown of the extracellular matrix and promotes cancer cell metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the use of gene expression analysis gave rise to different hypothesis on mechanisms used by HMGA1 in tumorigenesis. These studies have suggested the involvement of different signaling pathways such as the Ras/ERK, Wnt/b catenin, Notch, and Hippo signaling pathways in the action of HMGA1 (38,(40)(41)(42). However, most of these studies focused on the intracellular role of HMGA1 in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…To further clean the sample from the detergent present in the extraction buffer, protein pellets were loaded into a pre-cast 4–12% SDS gel and the electrophoretic run was stopped as soon as the protein extracts entered the running gel. They were then excised from the gels as single, narrow bands, and in situ digestion and peptide extraction were performed according to Resmini et al (2017). The resulting peptide solution was desalted on a C18 solid-phase extraction cartridge and 1 μg of each sample was analyzed by LC–MS/MS to check the digestion efficiency (details of the instruments and instrumental methods are given in the following section).…”
Section: Methodsmentioning
confidence: 99%